Vonal - Line - Linie - Ligne 1981. (Pécs : Pécsi Galéria, 1981)
Ameida, Helena ; Basset, Klaus ; Cooper, Waltraut ; Miklos, Erdély ; Ladislav Galeta, Ivan ; Tibor, Gayor ; Graham, Dan ; Kaitna, Walter ; Zsigmond, Károlyi ; Ilona, Keserü ; Kracht, Yvonne ; Krasinski, Edward ; Ferenc, Lantos ; Dora, Maurer ; János, Megyik ; Andras, Mengyán ; Mikolajczyk, Antoni ; Molnar, Vera ; Morellet, François ; Ridell, Torsten ; Robakowski, Józef ; László, Sáry ; Sommer, Ed ; Soto, Jesus Rafael ; Stazewski, Henryk ; Stembera, Petr ; Sýkora, Zdenék ; Trbuljak, Goran ; Tuttle, Richard ; Péter, Türk ; Wasko, Ryszard ; Weibel, Peter ; András, Koncz ; Ildiko, Enyedi ; Wise Ciobotaru, Gillian
Vonal - Line - Linie - Ligne 1981, Pécsi Galéria, Pécs, 26. April - 17 Mai 1981
boek